2015
DOI: 10.1186/s12974-015-0414-5
|View full text |Cite
|
Sign up to set email alerts
|

The nod-like receptor, Nlrp12, plays an anti-inflammatory role in experimental autoimmune encephalomyelitis

Abstract: BackgroundMultiple sclerosis (MS) is an organ-specific autoimmune disease resulting in demyelinating plaques throughout the central nervous system. In MS, the exact role of microglia remains unknown. On one hand, they can present antigens, skew T cell responses, and upregulate the expression of pro-inflammatory molecules. On the other hand, microglia may express anti-inflammatory molecules and inhibit inflammation. Microglia express a wide variety of immune receptors such as nod-like receptors (NLRs). NLRs are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 39 publications
1
57
1
1
Order By: Relevance
“…The authors demonstrated that Nlrp12 deficient mice are susceptible to dysbiosis and colitis and exhibit similar changes to those observed in EAE induction, with a loss of Lachnospiraceae family members and increases in the abundance of the Erysipelotrichaceae spp (Chen et al, 2017). Strikingly, Nlrp12 deficiency was also shown to exacerbate EAE (Gharagozloo et al, 2015, Lukens et al, 2015). It is possible that E2 treatment may therefore limit disease by similar mechanisms to Nlrp12, or indeed directly promote Nlrp12 expression.…”
Section: Discussionmentioning
confidence: 99%
“…The authors demonstrated that Nlrp12 deficient mice are susceptible to dysbiosis and colitis and exhibit similar changes to those observed in EAE induction, with a loss of Lachnospiraceae family members and increases in the abundance of the Erysipelotrichaceae spp (Chen et al, 2017). Strikingly, Nlrp12 deficiency was also shown to exacerbate EAE (Gharagozloo et al, 2015, Lukens et al, 2015). It is possible that E2 treatment may therefore limit disease by similar mechanisms to Nlrp12, or indeed directly promote Nlrp12 expression.…”
Section: Discussionmentioning
confidence: 99%
“…In encephalomyelitis NLRP12 negatively regulates the nuclear factor-kappa B (NF-kB) pathway suppressing inflammation [43].…”
Section: Microbesmentioning
confidence: 99%
“…Microglial and other myeloid lineage cells express innate immune response-related receptors [14][15][16]. Antigen recognition in innate immune response is mediated by pattern recognition receptors, such as NOD-Like Receptor Family Receptors (NLRs), which recognize Pathogen-Associated Molecular Patterns (PAMPs) and Danger-Associated Molecular Patterns (DAMPs) [17].…”
Section: Nlrp3 Inflammasomementioning
confidence: 99%